بناء نموذج ریاضی ثنائی البعد باستخدام طریقة العناصر المحددة لحساب تاثیر الاسنان الصخریة على قیم معامل ماننک للخشونة فی قناة رملیة ذات انحناء بسیط - عبدالحمید, عدی (Iraqi Journal of Civil Engineering, 2010)
In this research the finite element method is used to analyses the effect of groynes on the coefficient of Manning's value in meandering sandy channels is used. A two dimensional model of quadrilateral isoperimetric element is used, two meandering sandy channels were analyzed. The first channel has a central angle of ( 40o) with radius of curvature of (1.7m) , while the second channel has a central angle of ( 60o) with a radius of curvature of (2m) with a trapezoidal cross – section having a lower base of(1m) and side slope of ( 2H : 1V) and with bed slope of channels of ( 0.15% ). The main diameter of the sand used in this research of channels of (0.9mm ) achieved using observed data of Euphrates river at regulator of falluja. Five sections were located on each channels and four different discharges were passed through the two channels, the groynes sloped towards upstream were used in different locations at upstream and down stream of channels.